PERANAN KOMUNIKASI MELALUI PENYULUHAN TERHADAP KEMAMPUAN MASYARAKAT DALAM PENANGGULANGAN PENYAKIT TUBERKULOSIS DI KECAMATAN MEDAN MAIMUN - Roydi Nefri (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2017)
In this study, researchers study confirms the approach, methods and techniques used to gather and analyze information or data that will answer and explain the research problem to be studied. In this study used a qualitative study to explore the role of communication in the counseling for the prevention of tuberculosis disease. Development of a qualitative approach in research is based on giving meaning to the events observed, the expression of views and experiences of those involved in the study. This study uses informants in this study were selected carefully so relevant to the "Role of communication through counseling to cope with the disease Tuberculosis in Sub Field Maimoon" or in other words based on the selection of informants who can provide information or information about the problem being studied and can serve as participants in the research process.Based on the survey results revealed that the extension will contribute to the knowledge society in the District Tuberculosis disease prevention Maimoon Medan. Communication in the counseling community's ability to contribute to disease prevention in the District Tuberculosis Maimun Medan. Communities are able to communicate about how to manage Tuberculosis. Keywords :  Communication,  Cuonseling and Manage Tubercolusis